Pendampingan Literasi Keuangan Di MIS Al-Barokah : Membangun Kebiasaan Menabung Sejak Dini - Munir, Dede Rizal; Husna, Ade Irvi Nurul; Halimatussadiah, Halimatussadiah (Pusat Penerbitan LP2MPP ISI Bali, 2025)
This community service aims to enhance the understanding and saving habits among the students of Madrasah Ibtidaiyyah Al-Barokah through a financial literacy mentoring program. The activity took place on February 4, 2025, and included socialization, counseling, and hands-on activities such as creating piggy banks to foster a culture of financial literacy among children, with the goal of improving their understanding and instilling the habit of saving from an early age. The mentoring activities consisted of the opening and introductions, delivery of material on the importance of financial literacy, and a practical session on making piggy banks as a simulation of saving. This program successfully increased the students' understanding of financial literacy and their saving habits. The students' enthusiasm demonstrated that the material presented was well-received. The financial literacy mentoring program at Madrasah Ibtidaiyyah Al-Barokah was effective in building saving habits and raising awareness of the importance of financial management. It is hoped that this program can serve as a model for other schools.